Association Between Contrast Media Volume–Glomerular Filtration Rate Ratio and Contrast-Induced Acute Kidney Injury After Primary Percutaneous Coronary Intervention. (July 2015) - Celik, Omer; Ozturk, Derya; Akin, Fatih; Ayca, Burak; Yalcın, Ahmet Arif; Erturk, Mehmet; Bıyık, Ismail; Ayaz, Ahmet; Akturk, Ibrahim Faruk; Enhos, Asım; Aslan, Serkan
We hypothesized that contrast media volume–estimated glomerular filtration rate (CV–e-GFR) ratio may be a predictor of contrast media-induced acute kidney injury (CI-AKI). We investigated the associations between CV–e-GFR ratio and CI-AKI in 597 patients undergoing primary percutaneous coronary intervention (pPCI). An absolute ≥0.3 mg/dL increase in serum creatinine compared with baseline levels within 48 hours after the procedure was considered as CI-AKI; 78 (13.1%) of the 597 patients experienced CI-AKI. The amount of contrast during procedure was higher in the CI-AKI group than in those without CI-AKI (153 vs 135 mL, P = .003). The CV–e-GFR ratio was significantly higher in patients with CI-AKI than without (2.3 vs 1.5, P < .001). In multivariate analysis, independent predictors of CI-AKI were low left ventricular ejection fraction ( P = .018, odds ratio [OR] = 0.966), e-GFR <60 mL/min ( P = .012, OR = 2.558), and CV–e-GFR >2 ( P < .001, OR = 5.917). In conclusion, CV–e-GFR ratio is significantly associated with CI-AKI after pPCI.